The development and significance of art collectives in Malaysian contemporary art / Hawari Berahim … [et al.] - Berahim, Hawari; Ibrahim, Yuhanis; Ismail, Issarezal; Abdul Rahim, Haris Abadi; Ahmad Kamal, Nadya (Faculty of Art and Design, 2023)
Spanning over 90 years, the trajectory of art development in Malaysia encompasses the engagement of both early pioneers and emerging artists. Beginning in 2000, the emergence of art collectives has wielded substantial influence on the nation's contemporary art scene, establishing a platform for sharing ideas, goals, and collaborative ventures among artists. With a focus on challenging artistic norms, addressing societal concerns, and contributing to Malaysia's cultural mosaic, these collectives hold a clear purpose. The triumph of an art collective hinges on vital components like fostering community, mutual respect, a shared vision, and an effective organisational framework. The core objective of this study is to meticulously chronicle the establishment timeline of art collectives from 2000 to 2020, illuminating their membership and successful undertakings. Employing a methodology that combines various publication sources and insightful interviews, the research has identified more than 40 art collectives engaging in collaborative art pursuits. This collective endeavour seamlessly enriches the local contemporary art panorama, leaving an indelible mark on the industry's advancement.